(untitled) (Research, Society and Development, 2022)
The aim of the study was to evaluate how the specific cutting energy is influenced by the variation of the wood basic density in Eucalyptus spp. clones. Five clones, 10 years old, were used in the study: three hybrids of Eucalyptus grandis x Eucalyptus urophylla, one of Eucalyptus grandis and one of Eucalyptus urophylla. From each clone, five trees were cut down and divided into 2.0 m long logs. In two axial regions of the trunk (from 2.5 to 4.5 m and from 4.5 m to 6.5 m) the logs were cut into boards and reduced to specimens with dimensions of 660 x 110 x 21 mm. The basic density was determined by the hydrostatic method in two opposite wedges obtained from discs removed at 2.5, 4.5 and 6.5 m from the total height of the tree. To analyze the specific cutting energy, 10 specimens were selected for each axial region and clone. A frequency inverter was used to monitor the cutting process. Analysis of variance was applied to evaluate the specific cutting energy and the wood basic density. The results obtained appointed a significant difference between the woods of the clones for basic density and specific cutting energy. For the wood in the different axial regions, only the specific cutting energy was significant. Clone 1 required less specific cutting energy, as it was influenced by the lower basic density. In the 2.5 to 4.5 m axial region, a higher specific cutting energy was observed even with lower basic density.